Strategi Koping, Dukungan Petugas, dan Kesejahteraan Psikologis Anak Berkonflik dengan Hukum - Sri Maslihah (Psympathic : Jurnal Ilmiah Psikologi, 2018)
This study aims to obtain empirical data related to the influence of coping strategies and support officers in the formation of psychological well-being of conflicted-children with law. The Conflicted children with law is the children of the perpetrators of criminal acts and must undergo guidance in Protective Institution for children (LPKA). This research is a quantitative descriptive approach.  Subject of this study amounted to 43 conflicting children with the law who undergo guidance in LPKA Tangerang selected through purposive sampling technique. The measurement tool used in this study consists of the questionnaire of integrative well-being (Maslihah, 2017) , coping strategy (Moos, 2002),and officer support (Maslihah, 2017). The result of this study shows that when faced with pressing situation, psychological well-being can be influenced by coping strategy (internal factor) and officer support (external factor). Support officers can  serve as a moderator variable in the relationship of coping strategies and psychological well-being of conflicted children with law. Future research can analyze  based on cases of criminal acts committed by children accompanied by qualitative data.